The gut-lung axis: Gut microbiota changes associated with pulmonary fibrosis in mouse models induced by bleomycin - Quan, Yunyun; Yin, Zhujun; Chen, Shilong; Lang, Jirui; Han, Liyang; Yi, Jing; Zhang, Lu; Yue, Qianhua; Tian, Weiwei; Chen, Ping; Du, Shenglin; Wang, Jianbo; et al. (Frontiers in Pharmacology, 2022)
The main objective of this study was to investigate the alterations in the gut microbiota (GM) of pulmonary fibrosis (PF) mice induced by bleomycin (BLM) with its underlying mechanisms. BLM was docked with the targets of TGF-β/SMAD and caspase-3 pathways using the molecular docking technique. HE staining and Masson staining were applied to observe the histopathological changes in the pulmonary tissues. Detection of the apoptotic signals was conducted by flow cytometry and TUNEL staining. The mRNA expression of targets involved in the TGF-β/SMAD and caspase-3 signaling pathways in lungs was determined by qPCR. Immunohistochemistry (IHC) assay was used to detect the expression levels of cleaved caspase-3 and BAX proteins in mice lung tissues. 16S rDNA sequencing analysis was used to investigate the changes of GM in the fecal samples of mice in each group. The results showed that the apoptosis rate of pulmonary cells in the BLM group distinctly increased, with the expression levels of crucial target pro-apoptotic gene caspase-3, BAX with the corresponding protein, cleaved caspase-3, BAX were apparently elevated. This was accompanied by a significant increase in pro-fibrotic targets level such as TGF-β, fibronectin, collagen I, and collagen III. The mechanisms of PF induced by BLM were related to apoptosis of lung tissue cells such as alveolar epithelial cells and destroyed alveolar structure and excessive production of extracellular matrix (ECM), which may be bound up with activating TGF-β/SMAD and caspase-3 pathways. As for the GM, it was found that, after BLM induced PF in mice, the micro ecological balance of the GM was destroyed; the distance of PCo1 and Pco2 was significantly elongated, and the relative abundance of some intestinal probiotics like Catenibacterium and Lactobacillus (L. johnsonii and L. gasseri) dramatically lowered while the relative abundance of Verrucomicrobiales and Enterobacteriales substantially increased. Therefore, GM changes associated with PF in mouse models induced by BLM and the concept of “gut-lung axis” might provide an optional therapeutic strategy for PF.